Treatment strategies for post-infarction left ventricular free-wall rupture. Issue 4 (June 2019) - Matteucci, Matteo; Fina, Dario; Jiritano, Federica; Meani, Paolo; Blankesteijn, W Matthijs; Raffa, Giuseppe Maria; Kowaleski, Mariusz; Heuts, Samuel; Beghi, Cesare; Maessen, Jos; Lorusso, Roberto
Left ventricular free-wall rupture is one of the most fatal complications after acute myocardial infarction. Surgical treatment of post-infarction left ventricular free-wall rupture has evolved over time. Direct closure of the ventricular wall defect (linear closure) and resection of the infarcted myocardium (infarctectomy), with subsequent closure of the created defect with a prosthetic patch, represented the original techniques. Recently, less aggressive approaches, either with the use of surgical glues or the application of collagen sponge patches on the infarct area to cover the tear and achieve haemostasis, have been proposed. Despite such modifications in the therapeutic strategy and surgical treatment, however, postoperative in-hospital mortality may be as high as 35%. In extremely high-risk or inoperable patients, a non-surgical approach has been reported.